Towards the improvement of the methodology for assessing damage from soil contamination caused by emergencies and armed aggression - Krainiukov , O. M.; Matisko , B. Y. (Man and Environment. Issues of Neoecology, 2025)
Purposes. Analyze research on improving the methodology for determining the amount of damage from soil contamination due to emergencies and armed aggression.Results. Based on a analysis of the current regulatory framework, domestic and foreign scientific reserths, significant shortcomings of the current Methodology are outlined, in particular, limited consideration of soil degradation types, insufficient scientific validity of coefficients, and the absence of a comprehensive cost approach.Taking into account the potential impacts of hostilities on land resources and soil degradation, an attempt made to substantiate key proposals for improving the current methods for determining damage and losses caused to soil as a result of armed aggression.Conclusions.The need to include the costs of research, monitoring and analysis of pollution in the total amount of damage is argued. The proposed clarifications are aimed at increasing the accuracy of environmental accounting and forming sustainable principles of public management in the field of environmental restoration.